Private Activity in Latin America Declined Sharply But Became More Dispersed in 2010 - World Bank (Washington, DC, 2012)
In 2010, 54 infrastructure projects with private participation reached financial or contractual closure in 11 low and middle-income countries in Latin America and the Caribbean, involving investment commitments (hereafter, investment) of US$12.3 billion. Infrastructure projects implemented in the 1990-2009 period attracted new investment of US$21.9 billion, bringing total investment in infrastructure to US$34.2 billion in 2010. Such level of activity represents a 37 percent drop by investment and a 24 percent decline by the number of projects from 2009. The decline in regional activity was driven by the slowdown in new projects which saw their investment drop by 62 percent from 2009. Most of the decline in new projects occurred among large projects (US$500 million or more) which saw their investment fall by 76 percent in 2010 compared with 2009. By contrast, additional investment in projects implemented in 1990-2009 remained stable compared with 2009. Regional investment was less concentrated on Brazil and more widespread across other countries than in the previous year. Brazil saw its share in regional investment decrease from 81 percent in 2009 to 53 percent in 2010 due to a 59 percent decline in investment in the country. Certainly, Brazil accounted for the decline in regional investment. If Brazil were excluded, investment in the region would have grown by 50 percent in 2010 compared with 2009. The 11 countries with new projects in 2010 represented a larger geographic scope for new activity than in 2009 and 2008 when only eight countries implemented new projects each year. In 2010 Brazil had 18 new projects, Argentina and Mexico followed with eight and seven new projects, respectively. Chile, Colombia and Peru each had five new projects. Nicaragua had two projects while Guatemala, Honduras, Jamaica, and Panama each implemented one new project.